How Can User Reviews Support Learning from Experience? An Interactive Tool to Guide Accessibility in Mobile Applications - Oliveira, Alberto Dumont Alves; Campos, Ariel Emanuel Sebastian; Zaina, Luciana Aparecida Martinez; Eler, Marcelo Medeiros (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2025: Anais do XXIV Simpósio Brasileiro sobre Fatores Humanos em Sistemas ComputacionaisDO - 10.5753/ihc.2025.10961, 2025)
Introduction: Mobile applications are integral to daily life, yet designing accessible apps for users with disabilities remains challenging. While standards such as the Web Content Accessibility Guidelines (WCAG) exist, their complexity often limits adoption in fast-paced development. Objective: This paper presents A11YRevGuide (Accessibility User Reviews Guide), an interactive tool that links mobile accessibility guidelines with real user experiences from app store reviews. Methodology: Using the BBC Mobile Accessibility Guidelines, it organizes feedback into topics, enabling exploration of reported barriers and effective practices. Results: Visualizations such as tree diagrams, cards, and tables, combined with manual review analysis, connect formal guidance with lived experience. The tool supports inclusive app design, complements technical documentation with user evidence, and aligns with GranDIHC-BR 2025–2035 (Grand Challenge GC1).